Clinical features of COVID-19 in Italian outpatient children and adolescents during Parental, Delta, and Omicron waves: a prospective, observational, cohort study - Di Chiara, Costanza; Boracchini, Riccardo; Sturniolo, Giulia; Barbieri, Alessia; Costenaro, Paola; Cozzani, Sandra; De Pieri, Marica; Liberati, Cecilia; Zin, Annachiara; Padoan, Andrea; Bonfante, Francesco; Kakkar, Fatima; et al. (Frontiers in Pediatrics, 2023)
Introduction: COVID-19 features changed with the Omicron variant of SARS-CoV-2 in adultsCOVID-19 features changed with the Omicron in adults; however, data on children are limited to the early months of the Omicron wave. This study aims to describe COVID-19 symptoms in children and adolescents during the Parental, Delta, and Omicron eras. Methods: A single-centre, prospective observational study was conducted on individuals aged 0-20 years attending the University Hospital of Padua (Italy) from April 2020-to December 2022. COVID-19 cases were defined by positive SARS-CoV-2 molecular detection and/or serology; patient/family symptoms and virological positivity were considered to determine the infection onset. Variables were summarized and compared using appropriate tests of descriptive statisticsVariables were summarized/compared using descriptive statistics/the appropriate test. Results: A total of 509 cases (46% female, median age eight years [IQR: 4-12]) were studied. Three-hundred-eighty-seven (76%), 52 (10%), and 70 (14%) subjects experienced COVID-19 during the Parental, Delta, and Omicron waves, respectively. All subjects developed an asymptomatic/mild COVID-19. Overall, the most frequent symptoms were fever (47%) and rhinitis (21%), which showed a significant increasing incidence from the Parental to Omicron waves (p<0.001). Conversely, diarrhea was most common during diarrhea was commonest during the pre-Omicron eras (p=0.03). Stratifying symptoms according to the age groupStratifying symptoms according to age classes, fever, rhinitis, and skin rashes were observed more frequently among infants/toddlersskin rashes were higher in infants/toddlers; conversely, fatigue was more common conversely, asthenia and headache were more frequent in children older than five years. The duration of symptoms Symptoms' duration was similar across different SARS-CoV-2 variants of concern (VOCs); conversely, the number of symptoms varied according to the age group (p<0.0001)conversely, symptoms' numbers varied according to age classes (p<0.0001). Discussion: This study showed differences in COVID-19 clinical presentation among infants, children, and adolescents and confirmed Omicron infection is more likely to be associated with upper respiratory symptoms. However, further population-based studies are needed to support these findings. In addition, active surveillance will play a crucial role in assessing the disease severity of future VOCs.